Prognostic Analysis of Driving Style: The Significance of Demographic and Cognitive Factors - Justina Slavinskienė; Auksė Endriulaitienė (Psichologija)
This study aimed to compare four driving styles among professional and non-professional Lithuanian drivers and to assess the significance of demographic and cognitive factors in predicting investigated driving styles. The study included data from 446 nonprofessional drivers (mean of age 32.6 years) and 200 professional drivers (mean of age 47.7 years) in Lithuania. The research questionnaire comprised demographic data and self-report instruments for driving styles road risk perception and driving skills (perceptual-motor and safety) assessment. An interactive, video-based hazard prediction test was used to evaluate road hazard perception skills. The study results showed that professional drivers possess a more aggressive and more careless driving style, while nonprofessional drivers exhibited a more anxious driving style. It was found that longer driving experience, better self-assessed perceptual-motor skills, but poorer self-reported safety driving skills, were significant predictors for a driving style associated with a careless as well as with aggression, demonstrated among younger drivers. A poorer self-assessment of perceptual-motor driving skills was significantly associated with an anxious driving style among both professional and nonprofessional drivers with more driving experience. Finally, this study revealed that a safe driving style is significantly predicted by greater self-assessed perceptual-motor and safety driving skills.